Airborne characterization of subsaturated aerosol hygroscopicity and dry refractive index from the surface to 6.5 km during the SEAC4RS campaign. Issue 8 (29th April 2016) - Shingler, Taylor; Crosbie, Ewan; Ortega, Amber; Shiraiwa, Manabu; Zuend, Andreas; Beyersdorf, Andreas; Ziemba, Luke; Anderson, Bruce; Thornhill, Lee; Perring, Anne E.; Schwarz, Joshua P.; Campazano‐Jost, Pedro; et al.
Abstract: In situ aerosol particle measurements were conducted during 21 NASA DC‐8 flights in the Studies of Emissions and Atmospheric Composition, Clouds, and Climate Coupling by Regional Surveys field campaign over the United States, Canada, Pacific Ocean, and Gulf of Mexico. For the first time, this study reports rapid, size‐resolved hygroscopic growth and real refractive index (RI at 532 nm) data between the surface and upper troposphere in a variety of air masses including wildfires, agricultural fires, biogenic, marine, and urban outflow. The Differential Aerosol Sizing and Hygroscopicity Spectrometer Probe (DASH‐SP) quantified size‐resolved diameter growth factors (GF =  D p, wet / D p, dry ) that are used to infer the hygroscopicity parameter κ . Thermokinetic simulations were conducted to estimate the impact of partial particle volatilization within the DASH‐SP across a range of sampling conditions. Analyses of GF and RI data as a function of air mass origin, dry size, and altitude are reported, in addition to κ values for the inorganic and organic fractions of aerosol. Average RI values are found to be fairly constant (1.52–1.54) for all air mass categories. An algorithm is used to compare size‐resolved DASH‐SP GF with bulk scattering f (RH = 80%) data obtained from a pair of nephelometers, and the results show that the two can only be reconciled if GF is assumed to decrease with increasing dry size above 400 nm (i.e., beyond the upper bound of DASH‐SP measurements). Individual case studies illustrate variations of hygroscopicity as a function of dry size, environmental conditions, altitude, and composition. Key Points: Unprecedented aerosol hygroscopicity and refractive index data across North America up to several kilometers Narrow range of RI (real portion only) values (1.52–1.54) seen for all air mass classifications Modeling the evaporation of semivolatile species during aerosol particle measurements